2016
DOI: 10.1007/s10393-016-1116-x
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Infection and Diversity in Bats in the Australasian Region

Abstract: Following the SARS outbreak, extensive surveillance was undertaken globally to detect and identify coronavirus diversity in bats. This study sought to identify the diversity and prevalence of coronaviruses in bats in the Australasian region. We identified four different genotypes of coronavirus, three of which (an alphacoronavirus and two betacoronaviruses) are potentially new species, having less than 90% nucleotide sequence identity with the most closely related described viruses. We did not detect any SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 33 publications
5
50
0
Order By: Relevance
“…Our identification that individual Australian Myotis macropus were infected with a novel putative Alphacoronavirus over periods of epidemic models using the Myotis macropus mark-recapture data 17,19 , and found that both persistently and transiently infected bats were required for maintenance of coronaviruses.…”
Section: Persistent or Long-term Infection Of Australian Bat Coronavirusmentioning
confidence: 89%
See 1 more Smart Citation
“…Our identification that individual Australian Myotis macropus were infected with a novel putative Alphacoronavirus over periods of epidemic models using the Myotis macropus mark-recapture data 17,19 , and found that both persistently and transiently infected bats were required for maintenance of coronaviruses.…”
Section: Persistent or Long-term Infection Of Australian Bat Coronavirusmentioning
confidence: 89%
“…Subsequent to these ecological studies, we identified four putative novel coronaviruses (two Alpha-and two Betacoronaviruses) in seven species of Australian bats 17,18 . One of these species (Myotis macropus, Figure 1), had individuals infected with a putative novel Alphacoronavirus (detection of coronavirus RNA in faeces from bats enrolled in a mark-recapture study) over periods of up to 11 weeks, supporting the hypothesis for persistent or long-term infection as a method of maintaining coronaviruses in bats 17,19 .…”
Section: Persistent or Long-term Infection Of Australian Bat Coronavirusmentioning
confidence: 99%
“…Additionally, SARS-CoVr have been characterised from these three bat families (Pfefferle et al, 2009;Smith et al, 2016;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of horse races in Australia, research on P. alecto has received a lot of attention and strong government (Australia) support. In addition, P. alecto bats have been found to harbor other virus species potentially pathogenic to humans, including Lyssavirus, closely related to rabies virus13, previously unknown paramyxoviruses14 as well as a novel betacoronavirus15. Serological evidence of infection with Menangle virus (MenV) in Pteropus spp.…”
mentioning
confidence: 99%